Benign fibrous histiocytoma of the tongue: a case report - Brantes, Michele Fonseca; Azevedo, Rebeca Souza; Oliveira, Silvia Paula; Gouvêa, Adriele Ferreira; Takahama Jr, Ademar (Brazilian Dental Science, 2017)
The fibrous histiocytoma is a soft tissue neoplasm that affects the dermis and the subcutaneous tissue, rarely is found in the oral cavity and perioral regions, and is originated from the proliferation of fibroblasts and histiocytes. The objective of this paper is to report a case of Benign Fibrous Histiocytoma in a 30-year-old male patient, complaining of a painless nodule in the tongue for about six months. With the clinical diagnostic hypotheses of Fibrous Hyperplasia or Traumatic Neuroma an excisional biopsy was performed. The histopathological examination revealed a non-encapsulated proliferation of spindle cells with some giant multinucleated cells in the periphery of the lesion. Immunohistochemical reactions were performed, staining only for vimentin in the spindle cells and for CD68 in the multinucleated giant cells. According to these characteristics, the final diagnosis was Benign Fibrous Histiocytoma. The correct diagnosis of spindle shaped cell neoplasia must be performed with the aid of histopathological analysis and immunohistochemistry, mainly because the morphological similarities with other benign and malignant lesions.